Strategi Pemasaran Digital Melalui Media Sosial Instagram pada UMKM di Era Digital - Yanti Fitria (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2022)
Advances in information technology have transformed the way micro, small, and medium enterprises (MSMEs) market their products and reach consumers. One effective strategy for competing in the digital era is the utilization of social media, particularly Instagram. This study aims to analyze the digital marketing strategies implemented by MSMEs on Instagram and evaluate their impact on enhancing brand awareness and product sales. The research employed a descriptive qualitative approach, with data collected through literature reviews and observations of the digital marketing activities of several local MSMEs in Palembang. The results showed that digital marketing strategies emphasizing creative content, customer interaction, and the use of Instagram features such as stories, reels, and influencer marketing enhanced brand visibility and strengthened relationships with consumers. This study confirms that the optimal use of social media can serve as an effective strategy for MSMEs to adapt and thrive within the competitive digital economy ecosystem.